Impact of mechanical circulatory support on post-transplant stroke risk. Issue 10 (October 2021) - Nair, Nandini; Yang, Shengping; Gongora, Enrique
The effect of type of mechanical circulatory support on stroke risk during the early post-transplant period remains undefined in patients bridged to transplant. This study assesses if the type of circulatory support device affects stroke risk in this population. The study cohort of 4257 adult patients bridged with mechanical support to cardiac transplant were derived from the UNOS transplant registry data. Risk factors assessed were age, gender, ischemic time, diabetes (recipient), durable mechanical support at listing and mechanical ventilation pre-transplant. Descriptive statistics were used to describe characteristics of the study cohort. Univariate logistic regression was used to test if there is a significant association between stroke event and all the potential risk factors. Multivariate logistic regression was used to test such associations while adjusting for all other risk factors. Odds ratios (ORs) and their 95% confidence intervals (CIs) in parenthesis, were calculated. p  < 0.05 was considered significant. Patients on Extracorporeal membrane oxygenation (ECMO) had the highest risk of stroke immediately post-transplant prior to discharge (OR 3.03, {1.16, 7.95}) followed by Total Artificial Heart (TAH) (OR 2.03, {1.01, 4.07) as compared to those only on a Left Ventricular Assist Device (LVAD). Ischemic time (OR 1.3 {1.09, 1.45}) and diabetes (OR 1.8 {1.29, 2.51}) were significant risk factors. Patients on ECMO and TAH had a 203% and 103% increase respectively in the odds of having a stroke prior to discharge as compared to those only on LVADS.